Schopenhauer: On individuals and Society - Carrillo Castillo, Lucy (Estudios de Filosofía, 2008)
Schopenhauer`s Moral Philosophy is a critique to society that can be approached from two perspectives. On the one hand, from the bases of Metaphysical Pessimism where his Critique of the State finds support, in sum, conventions and prejudices which Schopenhauer calls the fundamental selfishness of the human condition. (1. The schopenhauerian concept of philosophy. 2. The critical character of his Moral Philosophy.) But, on the other hand, from what can be termed his effort to think a dialectical conciliation between vita activa et vita contemplative, where the ethical sense of his philosophy finds an indication of its possibilities when Aesthetics is to be considered. (3. The concept of compassion. 4. Schopenhauers actuality).